Colloidal synthesis and characterisation of oleic acid capped TiO2 nanorods. (2017) - Ananthakumar, S.; Kumar, J. Ram; Babu, S. Moorthy
Oleic acid (OLA) capped TiO2 nanorod-like structures were synthesised in the presence of titanium tetra-isopropoxide (TTIP) as the titanium source at the temperature of 110°C. Strong bases trimethyl amino-N-oxide (TMAO) and tetrabutyl ammonium hydroxide (TBAH) were used to hydrolyse the titanium source. In both cases, the formation of anatase phase was confirmed and through the extremely narrow width of the (004) peak compared to (200) and (211), the formation of rod like structure along c-axis growth was confirmed. The prepared nanorods were dispersed in chloroform (CHCl3 ) and UV-Visible spectra of the powdered TiO2 NRs-like structure and dispersed in solvent show the indirect band gap of 2.60 eV and 2.73 eV. High resolution scanning electron spectroscopy (HRSEM) analysis indicates the formation of agglomerated nanoparticles with the non-spherical shape. Transmission electron spectroscopy (TEM) analysis confirms that the nanorods-like structures were around 10 nm diameter and around 80 nm in length. Thermogravimetric analysis-differential thermal analysis (TG-DTA) confirms the loss of ligand oleic acid at 400C. Attenuation total reflectance-Fourier transform infra-red (ATR-FTIR) spectra analysis further confirms the attachment of the ligand on the nanoparticles' surface. The possible mechanism of the formation of TiO2 nanorods-like structure was analysed. The results are discussed in detail.